Measurements of interactions of membrane proteins - Hagen, Guy M., author; Barisas, B. George, advisor (Colorado State University. Libraries, 2005)
We have improved upon conventional fluorescence photobleaching recovery (FPR) measurements by introducing two new techniques: total internal reflection interference fringe (TIRIF)-FPR, and high probe intensity (HPI)-FPR. Both of these techniques are designed to enhance diffusion measurements of visible fluorescent protein (VFP)-membrane receptor fusion proteins. TIRIF-FPR restricts photoexcitation to the cell membrane, eliminating contributions to the recovery signal from fluorescent cytoplasmic species. HPI-FPR accomplishes measurements of sparsely-expressed VFP-fusion proteins where conventional measurements fail by increasing laser power in spot-FPR methods. Data with increased fluorescent probe photobleaching in the attenuated measurement beam are thus recorded, and for the first time, correctly evaluated. We have compared both new and existing FPR techniques on a variety of biological systems including measurements of the mast cell function-associated antigen (MAFA). This regulatory protein is involved in IgE-receptor mediated allergic responses and was also studied using time-resolved phosphorescence anisotropy (TPA) methods. TPA results, which are uniquely sensitive to in-membrane molecular size, indicate the IgE receptor and the MAFA regulatory protein are linked in the membrane under both resting and activating conditions. As part of an on-going effort to improve TPA measurements, new strategies for photomultiplier tube (PMT) gating have also been devised. Saturation of the photomultiplier used in TPA measurements during the intense visible laser flash is a serious problem which can cause artifactual signals and damage to the detector. This was previously addressed by rapidly gating the detector off, but artifactual signals arising at the end of the off-gated period persisted. We have thus developed a fast, fully adjustable photomultiplier gate with high extinction that is capable of eliminating the light-induced post gate artifacts encountered with earlier gating techniques.
Keywords: analytical chemistry; cellular biology; biochemistry